The Evaluasi Usability Aplikasi Goapotik Menggunakan Metode System Usability Scale (SUS) - SUBEKTI, REGI MUKLIS; Khaira, Ulfa; Noverina, Yolla (JUSS (Jurnal Sains dan Sistem Informasi), 2026)
Digital transformation in the healthcare sector has driven the emergence of mobile-based health service applications such as GoApotik, which facilitates the online purchase of medicines and health products. Although it holds a 4.6 rating on the Play Store, several user complaints regarding application responsiveness, order processing by partner stores, lengthy refund times, and address feature errors indicate the need for an in-depth usability evaluation. This study aims to measure the usability level of the GoApotik application and provide a comprehensive overview of the evaluation results using the System Usability Scale (SUS) method. The research employed a quantitative method involving 100 active GoApotik user respondents in Muaro Jambi Regency and Jambi City, selected through nonprobability sampling with a quota sampling approach, using a ten-item SUS questionnaire distributed via Google Form. The results show an average SUS score of 81.875, with a maximum score of 90 and a minimum of 45, categorized as Excellent, grade B+, 83rd percentile, Acceptable, and Promoter on the Net Promoter Score. Among the five usability dimensions, Efficiency, Memorability, and Satisfaction scored high, while Learnability and Errors remained relatively low, particularly among digital immigrant users. It is concluded that GoApotik demonstrates a good level of usability; however, adding interactive tutorial features and expanding respondent coverage in future research are recommended.